Energy Consumption Analysis of DBR and VBF Protocols in Underwater Sensor Networks Using Aqua-Sim at Network Simulator 2 - Ahmad Tsaqib Hakim; Arrum Prima Dewi; Doan Perdana; Cyril Nugrahutama Kurnaman (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
For decades, there have been significant interests in monitoring the aquatic environment for scientific exploration, commercial exploitation, coastline protection, and even disasters prevention and mitigation such as tsunami warnings. Highly precise, real-time, and temporal-spatial continuous aquatic environment monitoring system is extremely important for underwater life. To support and simulate such monitoring system, underwater sensor networks (UWSN) have emerged as a very powerful technique for many applications on underwater environment, including monitoring, measurement, surveillance, and control by using Aqua-Sim. Aqua-Sim is a simulator for UWSN developed on Network Simulator 2 platform which effectively simulates the attenuation of underwater acoustic channels and the collision behaviors in long delay acoustic networks. Currently, there are several routing protocols for UWSN which are implemented in Aqua-Sim. On this research, we did a simulation on Aqua-Sim by performing Vector-based Forwarding (VBF) protocol and Depth-based Routing (DBR) protocol performance analysis based on energy consumption parameter. Based on the result, it can be concluded that the VBF routing protocol requires more energy consumption than the DBR routing protocol.